Development stages and legal framework of public investment policy of the Republic of Korea - Ikramova, Mehribon (International research journal of management, IT and social sciences, 2021)
The practice of foreign countries confirms that with the effective use of attracted foreign investment, there is a change in the nomenclature of production and exports from raw materials in favor of goods with high added value, an increase in the international competitiveness of the economy and the welfare of the population. Countries with well-designed policies to stimulate FDI inflows perform the most positively in terms of economic growth. One of these countries is the Republic of Korea.